2022
DOI: 10.1186/s44147-022-00120-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of novel Coanda-based unmanned aerial vehicle

Abstract: Conventional Coanda-based unmanned aerial vehicles (UAV) experience thrust losses in the radial direction. To address these losses, a rectangular, linear arrangement of the Coanda surface was adopted in the proposed novel design. This arrangement minimizes the area change in the radial direction to recover such thrust losses. A prototype of the proposed UAV structure was 3D printed and assembled with a single 9-inch propeller. Performance characteristics of the UAV were evaluated through static testing on a dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It is observed that the use of unmanned aircraft has had unprecedented growth in a wide class of manufacturing, including mainly commercial and military. Most designers aim to perfect the aerodynamic operation of their design to provide greater payload, power, and range (Siddiqi & Lee, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the use of unmanned aircraft has had unprecedented growth in a wide class of manufacturing, including mainly commercial and military. Most designers aim to perfect the aerodynamic operation of their design to provide greater payload, power, and range (Siddiqi & Lee, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…MRF simulations are sufficient for thrust and torque prediction of an open propeller and can reduce the CPU time of rigid body motion simulations [27]. In the rotation domain, the flow around a propeller by assigning a constant rotational velocity while the solid structure of the propeller itself remains fixed [28][29][30][31].…”
Section: Mesh and Cfd Setupmentioning
confidence: 99%
“…Current research is focused on optimizing Coanda surface design for UAVs, particularly exploring novel configurations for enhance thrust/ lift performance. This is the case of two studies that used linear rectangular and straight cylindrical surface arrangements to improve performance by 17% to 45%, respectively [24][25]. Moreover, the Coandȃ effect is also being tested nowadays in helicopters with no tail rotor as in NOTAR [20][21][22][23][24][25][26] or in spherical drones propelled by closed impellers utilizing the Coanda effect [27].…”
Section: State Of the Artmentioning
confidence: 99%
“…This is the case of two studies that used linear rectangular and straight cylindrical surface arrangements to improve performance by 17% to 45%, respectively [24][25]. Moreover, the Coandȃ effect is also being tested nowadays in helicopters with no tail rotor as in NOTAR [20][21][22][23][24][25][26] or in spherical drones propelled by closed impellers utilizing the Coanda effect [27]. The benefit of using the Coandȃ effect with a single rotor also effectively reduces noise, offering a potential breakthrough for acoustical stealth in drone operations compared to conventional multi-rotor systems [28].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation